Characterization of citronella grass essential oil of Cymbopogon winterianus from Batang region, Indonesia. (April 2020) - Kusumaningrum, H P; Zainuri, M; Endrawati, H; Purbajanti, E D
Abstract: The needs of herbal medicine tend to increase because of their little side effect and complications. Citronella oil has been under an attention due to progressive need for new biochemical effects to establish a novel production from this essential oil. The chemical properties of essential oil of Citronella grass from Batang Indonesia, distilled from leaves and shoots of Cymbopogon winterianus were found to be within the specifications set by Indonesia National Standart for Essential Oil. The result of GC-MS analysis showed 30 component with the major components of essential oil: Isopulegol, Tricyclo[5.2.1.0(1, 5)]decane, LINALOOL L, Butanoic acid, Citronellyl acetate, Geranyl acetate, and Elemol. Comparison with commercial citronella oil showed different concentrations in the essential oil of Citronella grass from Batang Indonesia. Essential oil of Citronella grass from Batang Indonesia was also showed antimicrobial and dermatophic activity according to PASS analysis.